Estudo comparativo das propriedades reológicas e mecânicas dos concretos produzidos com diferentes aditivos redutores de água - Marcio Eurelio de Paiva Oliveira (2016)
Concrete is one of the materials sold worldwide, and the production of concrete companies is expected to reach 72.3 million m3 in 2017, and its components are obtained from non-renewable sources such as aggregates, cement and water. Reducing the consumption of water and cement per cubic meter of concrete is extremely important from the point of view of the unit cost of production and also from the point of view of sustainability, aimed at reducing the consumption of raw materials, the generation of environmental impacts and also the production ofmore durable concrete. New technologies and the development of chemical additives have greatly reducing water consumption and consequently the consumption of cement per cubic meter of concrete with the same water / cement ratio. The use of polycarboxylate-based additives can reduce up to 40% of water consumption in concrete dosages when compared to those without any additive. The objective of this research is to compare the rheological and mechanical properties of three types of concrete with the same water / cement ratio containing three types of reducing chemical additives more water used in the market (based on lignosulphonate, mixed base and the base of polycarboxylate ). rheological parameters such as retention of workability as measured by the Abrams cone trunk rebate were studied, the entrained air content, and the start and end times handle, in addition to mechanical properties such as compressive strength, tensile strength in bending and modulus of elasticity. Also the physical properties were evaluated: water absorption, voids and density of the concrete. It was observedthat the compressive strength decreased as the consumption of water and cement per cubic meter were reduced to concrete with the same water / cement ratio. The modulus of elasticity and tensile strength in bending of the polycarboxylate concrete improved with the presence of the additive. The absorption and void ratio also decreased in the concrete with the polycarboxylate additives, making them more durable, since these properties reduce hinders the migration of aggressivesubstances such as chlorides and carbonation.